2005
DOI: 10.3354/meps296143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sediment source and flow regime on clam and sediment transport

Abstract: Erosion and transport of juvenile benthic invertebrates, including bivalves, has the potential to alter patterns of distribution and abundance during the early postsettlement period. Field observations indicate that there is often great spatial variability in rates of transport of juvenile bivalves. Differences in transport among sites may arise from both physical and biological causes, including variation in water flow, sediment grain size, and the local biological community. In this study, an experiment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…This suggests that dispersal of these species of juvenile bivalves (of which Gemma gemma are the most abundant) is primarily initiated by sediment erosion and occurs as bedload transport. Other studies also have found strong relationships between sediment transport and bivalve transport in the field (Emerson & Grant 1991, Commito et al 1995a, b, Hunt & Mullineaux 2002 and the laboratory (Hunt 2005). This type of relationship occurs in other groups of macrofauna (e.g.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…This suggests that dispersal of these species of juvenile bivalves (of which Gemma gemma are the most abundant) is primarily initiated by sediment erosion and occurs as bedload transport. Other studies also have found strong relationships between sediment transport and bivalve transport in the field (Emerson & Grant 1991, Commito et al 1995a, b, Hunt & Mullineaux 2002 and the laboratory (Hunt 2005). This type of relationship occurs in other groups of macrofauna (e.g.…”
Section: Discussionmentioning
confidence: 87%
“…Rates of transport were low at Sites 2 and 4, where the sediment was covered with tubes created by the amphipod Ampelisca abdita. In the laboratory, Hunt (2005) found that erosion of juvenile Mya arenaria and sediment collected from the 4 sites used in the present study varied strongly among sites at a common shear velocity, likely due to an effect of the amphipod mats on sediment erosion. Mats created by this amphipod may impact bivalves significantly.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Invertebrate biomass at Barnstable Harbor is dominated by direct-developing gem clams (Gemma gemma), two polychaetes with short-lived demersal larvae (Clymenella torquata and Glycera dibranchiata), and perhaps paradoxically, intertidal mud snails (Nassarius obsoletus) with planktonic larvae (Sanders et al, 1962). Juveniles and larvae of the first three species have never been observed to venture into the water column except by resuspension (e.g., Hunt, 2005) and would have limited transport in the harbor. In contrast, mud snail larvae spend 2-4 weeks in the plankton before they become competent to metamorphose (Scheltema, 1967).…”
Section: A Field Environmentmentioning
confidence: 99%